Video Versus Direct Laryngoscopy for Tracheal Intubation of Critically Ill Adults: A Systematic Review and Meta-Analysis - Polo, Paola P. (2025)
Background/Objectives: Endotracheal intubation in critically ill patients presents significant challenges due to anatomical and physiological complexities, making airway management crucial. Video laryngoscopy (VL) has emerged as a promising alternative to direct laryngoscopy (DL), offering improved and higher success rates. This systematic review and meta-analysis evaluated the comparative efficacy and safety of VL versus DL in critically ill adults. Methods: A systematic search was conducted in PubMed, Embase, and Cochrane Library through August 2024 following PRISMA-2020 guidelines. Randomized controlled trials comparing VL and DL in critically ill adult patients were included. The RoB 2.0 tool assessed bias, and GRADE evaluated the certainty of evidence. The primary outcome was first-attempt success; secondary outcomes included intubation time, glottic visualization, and complications. Random effects models were used for data synthesis. Results: Fifteen studies (4582 intubations) were included. VL improved first-attempt success rates (RR 1.12; 95% CI: 1.04–1.21; I2 = 87%). It also reduced esophageal intubation (RR 0.44; 95% CI: 0.26–0.75), dental injuries (RR 0.32; 95% CI: 0.16–0.67), and poor glottic visualization. No significant differences were found in hypoxemia, hypotension, or mortality. Conclusions: VL enhances intubation success and reduces specific complications, particularly in difficult airways. However, high heterogeneity and low certainty of evidence warrant further studies to clarify its impact on critical patient outcomes.